"Glorious Mothers" and "Rational Women": A Comparative Analysis of the Chinese and English Regulatory Models of Abortion. (26th February 2020) - Cao, Weiwei
Abstract: Access to safe abortion is essential to satisfy women's need for healthcare and control over their life choices. Modern regulation of abortion appears to be female friendly because it abandons the old oppressive appearance and wears a liberal face. By examining the images of "glorious mothers" and "rational women" constructed by the Chinese and English regulatory models of abortion through a feminist lens, this Article aims to offer a more critical response to the two jurisdictions. Furthermore, by comparing the two models of abortion law, the Article provides feminists and reformers with a chance to learn about each other's experiences and different regulatory strategies. As a result, they will be able to view the merits and shortcomings of their national abortion law from a fresh angle. Finally, this comparative study offers a basis for feasible law reform proposals that would empower women in decision making concerning abortion.